2016
DOI: 10.5665/sleep.5322
|View full text |Cite
|
Sign up to set email alerts
|

Inverse U-shaped Association between Sleep Duration and Semen Quality: Longitudinal Observational Study (MARHCS) in Chongqing, China

Abstract: Either restricted or excessive sleep may impair semen quality. Further research is needed to validate this finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(78 citation statements)
references
References 34 publications
3
66
4
Order By: Relevance
“…Kim et al 2016, Niijima et al 2016); however, it is different to the ones reported for some other pathologies where a U-shaped (e.g. Li et al 2015, Chen et al 2016 or an inverse linear association was reported (e.g. King et al 2008).…”
Section: Interpretation In the Context Of Available Literaturecontrasting
confidence: 62%
“…Kim et al 2016, Niijima et al 2016); however, it is different to the ones reported for some other pathologies where a U-shaped (e.g. Li et al 2015, Chen et al 2016 or an inverse linear association was reported (e.g. King et al 2008).…”
Section: Interpretation In the Context Of Available Literaturecontrasting
confidence: 62%
“…Regular and adequate sleep is important for normal physiology, but its role in human semen quality is not clear. In a longitudinal study, the investigators suggested that both restricted and excessive sleep had negative impact on semen quality (Chen et al, ; Liu et al, ). Sleep duration was not associated with any of the semen parameters in our study.…”
Section: Discussionmentioning
confidence: 99%
“…These include increased risk of cardio-metabolic complications, hypertension, obesity, type 2-diabetes, cardiovascular disease, urologic complications, cancer, and depression [1][2][3][4][5][6]. Results from a limited number of recent studies suggest that inadequate bedtimes, short sleep duration, and poor sleep, assessed as poor self-reported sleep quality, may impact semen quality [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Sleep duration itself has been linked to semen quality in fertile [9] and in infertile [13,14] men. Chen et al [9] found the optimal sleep duration to be 7.0-7.5 h in 796 Chinese fertile men. Green et al [14] found a positive correlation between sleep duration and total sperm and motility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation